2022
DOI: 10.1001/jamanetworkopen.2022.18981
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Poor Mental Health Among Adolescents in Kabul, Afghanistan, as of November 2021

Abstract: This study has some limitations. Owing to heightened security, we were unable to adopt a random-sampling design, we could only recruit from Kabul, it was difficult to recruit girls, the sample size was limited, and the cross-sectional design precluded any inference of causation. Follow-up studies are needed to monitor the chronicity of psychiatric disorders among adolescents in Afghanistan.Adolescents in Afghanistan, especially girls, are experiencing significant mental health problems. However, Afghanistan's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 3 publications
2
14
1
Order By: Relevance
“…Secondary outcomes were assessed using the Revised Children’s Manifest Anxiety Scale (anxiety), Strengths and Difficulties Questionnaire (psychiatric difficulties), and Afghan Symptom Checklist (culture-specific idioms of distress) . All measures have been used with Afghan youth, and internal consistency was good (McDonald ω > 0.78) (eMethods in Supplement 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary outcomes were assessed using the Revised Children’s Manifest Anxiety Scale (anxiety), Strengths and Difficulties Questionnaire (psychiatric difficulties), and Afghan Symptom Checklist (culture-specific idioms of distress) . All measures have been used with Afghan youth, and internal consistency was good (McDonald ω > 0.78) (eMethods in Supplement 2).…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted following these sociopolitical changes found, among a sample of 376 adolescents, approximately half met criteria for PTSD, depression, or anxiety, 15 with more girls vs boys meeting criteria for PTSD (79.4% vs 31.0%) and depression (79.4% vs 26.4%). 15 The developmental process of being an adolescent in Afghanistan can be very difficult. 9 Addressing psychiatric concerns during adolescence is imperative, 4,5,16 particularly as the wellbeing of adolescents and their ability to contribute to society is essential for the prosperity of Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies assessed the impact of MHPSS programmes in the aftermath of disasters. Only four studies aimed to measure the impact of MHPSS programmes on young women and girls (SHoaakazemi et al, 2012; O’callaghan et al, 2013; Robjant et al, 2019; Ahmadi et al, 2023) and only one study focused on former child soldiers and war-affected boys (McMullen et al, 2013). Most MHPSS programmes were delivered in school or classroom.…”
Section: Resultsmentioning
confidence: 99%
“…In a sample of 376 high school children in Kabul, approximately half met the criteria for a probable diagnosis of PTSD ( n = 194, 51.6%), depression ( n = 184, 48.9%) or anxiety ( n = 170, 45.2%). 58…”
Section: Resultsmentioning
confidence: 99%